DEVELOPMENT OF RARERIPE PEQUI FRUIT (Caryocar brasiliense) IN THE SOUTH OF MINAS GERAIS STATE, BRAZIL - Rodrigues, Luiz José (2009)
The objective of this research was the characterization of rareripe pequi fruits, along its development. The fruits were collected 12 km away from Itumirim, south of Minas Gerais State, Brazil (21º19’01”S, 44º52’16”W, 871 m altitude), at intervals of fifteen days, from anthesis to fruit abscission. Pequi fruit blooming started in May and peaking in June. Early fruit began in July, and most of the ripe fruits was found in August. The period from flower opening (anthesis) to fruit abscission was 117 days. The coordinates L* and a* increased values, showing changes in peel coloration from dark green (L* = 5.76 and a* = -24.83) to light green (L* = 24.83 and a* = -6.32). Fruits reached maximum size at 102 days after anthesis, with mass of 109 g, 6.45 cm of longitudinal diameter, and 6.50 cm of transversal diameter. Pequi is a fruit with an extremely high respiratory activity, presenting respiration of 67.01 mL.CO2. Kg-1.h-1, at 117 days after anthesis. KEY-WORDS: Caryocar brasiliense; savannah-like vegetation; physical parameters; respiratory rate; growth pattern.